A-07 Race, SES, and IQ Test Score Differences: The Case for Social Justice. (28th August 2020) - Weiss, L
Abstract: Objective: To quantify potential mediators of observed IQ test score differences of Whites with Hispanics and African Americans in the WISC-IV, WISC-V, and WAIS-IV standardization data sets. Method: Mediators included parent education, income and academic expectations for children and adolescents; and self-education, income and occupation for adults. Observed IQ score means are presented by race and ethnicity, unadjusted for demographics. A series of regressions quantify the variance in IQ test scores accounted for by race/ethnicity before and after controlling for SES related mediators. Results: SES related mediators accounted for substantial portions of IQ score variance in all group comparisons and age ranges, but least for African Americans and adults. Conclusions: The critical influence of cognitively enriching and impoverishing environments on the neurocognitive development of children, and the unequal distribution of these influences across social and economic groups are discussed as complementary with interpretations of acculturation and heredity.